Some results on the uniform boundedness theorem in locally convex cones - Saiflu, H.; Ranjbari, A. (Methods of Functional Analysis and Topology, 2009)
Walter Roth studied one form of the uniform boundedness theorem in Rot98. We investigate some other versions of the uniform boundedness theorem for barreled and upper-barreled locally convex cones. Finally, we show some applications of this theorem.